2007
DOI: 10.1007/s10741-007-9005-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diabetes on cardiac β-adrenoceptor subtypes

Abstract: Despite the significant developments in the treatment of diabetes mellitus, diabetic patients still continue to suffer from cardiac complications. The increase of cardiac adrenergic drive may ultimately contribute to the development and progression of diabetic cardiomyopathy. beta-Adrenoceptors play an important role in the regulation of heart function. However, responsiveness of diabetic heart to beta-adrenoceptor agonist stimulation is diminished. The chronotropic responses mediated by beta(1)-subtype, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 71 publications
4
35
1
1
Order By: Relevance
“…Cardiac function and left ventricular pressure characteristics were comparable with those of healthy control mice at baseline conditions, but the inotropic and lusitropic responses to dobutamine stress test were attenuated in adult type 2 diabetic mice (8). Downregulation of adrenoceptor-␤1 induced by diabetes was speculated to cause these cardiovascular changes (1). However, in our study, fetal Adrb1 expression was not affected by maternal hyperglycemia and is thus unlikely to contribute to the observed reduction in FHR.…”
Section: E615supporting
confidence: 44%
“…Cardiac function and left ventricular pressure characteristics were comparable with those of healthy control mice at baseline conditions, but the inotropic and lusitropic responses to dobutamine stress test were attenuated in adult type 2 diabetic mice (8). Downregulation of adrenoceptor-␤1 induced by diabetes was speculated to cause these cardiovascular changes (1). However, in our study, fetal Adrb1 expression was not affected by maternal hyperglycemia and is thus unlikely to contribute to the observed reduction in FHR.…”
Section: E615supporting
confidence: 44%
“…Many neurotransmitters and neurohormones also exert regulatory effects on the biochemical and physiological processes in the CNS and in the periphery via ACSS. It was shown by us and the other authors that the changes in ACSS activity in diabetic tissues correlate positively with severity and duration of DM2 [3036]. Therefore, the study of ACSS is one of the most promising approaches to be used in the case of DM2 for identification of functional abnormalities in the CNS and the periphery as well as for monitoring dysfunctions in the nervous, cardiovascular, and other systems and for evaluation of the effectiveness of antidiabetic therapy [13, 31, 32, 37].…”
Section: Introductionmentioning
confidence: 96%
“…An important role in the etiology and pathogenesis of DM2 and its complications is assigned to alterations in the brain and peripheral hormonal signaling systems, the hormone-sensitive adenylyl cyclase signaling system (ACSS) in particular [3032]. The ACSS plays a key role in the regulation of contractile function of the heart by adrenergic agonists.…”
Section: Introductionmentioning
confidence: 99%
“…One of the causes of these complications is the alterations in hormone-sensitive signaling systems, the adenylyl cyclase (AC) system in particular [3,4]. It was shown that changes in the functional activity of AC system in the heart, brain, and reproductive tissues in experimental T1DM were tissue and hormone speci�c [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%